Intensity and direction dimensions of competitive state anxiety: A time-to-event approach - Stavrou, N.A.a b; Psychountaki, M.a; Zervas, Y.a (Perceptual and Motor Skills, 2006)
The purpose of the present study was to examine the temporally patterned changes in intensity and direction of competitive state anxiety prior to and during competition as well as correlations among intensity and direction on the Competitive State Anxiety Inventory-2D subscale scores. 99 athletes completed the inventory one day before and an hour before the competition, based on how they felt during that time, and 30 min. after the competition with reference to how they felt during the competition. Analysis indicated different temporal patterning in subscale scores prior to competition. Correlations were medium (.40) for Intensity and Direction dimensions. Significant differences were noted between scores of those classified as Facilitators and Debilitators on the Intensity dimension. The results support the multidimensional nature of competitive anxiety, Moreover, additional information lies in directional interpretation of competitive anxiety and self-confidence. © Perceptual and Motor Skills 2006.
Keywords: Adolescent; Adult; anxiety disorder; Anxiety Disorders; article; Cognition; competitive behavior; Female; Hospitalization; human; Humans; Male; questionnaire; Questionnaires; self concept; Severity of Illness Index